Trichinella Infection in Wildlife of Northeast of Iran - Borji, H (Tehran University of Medical Sciences, 2012)
BACKGROUND: The objective of this investigation was to detect the presence of Trichinella in some carnivores of Mashhad in northeast of Iran and to identify Trichinella species circulating in this area. METHODS: The present study was carried out using muscle tissue collected from 120 stray dogs, 26 wild boars, 25 rodents, two foxes and two hyenas captured in Mashhad City, province of Khorasan Razavi, Iran. RESULTS: Trichinella larvae were detected in three stray dogs by artificial digestion and compression. All larvae were identified as T. britovi using multiplex PCR. CONCLUSION: This is the first report of identification of T. britovi in stray dog in Iran.